2021
DOI: 10.1038/s41598-021-84425-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial carbon source utilization in rice rhizosphere soil with different tillage practice in a double cropping rice field

Abstract: Carbon (C) plays an important role in maintaining soil fertility and increasing soil microbial community, but there is still limited information about how source utilization characteristics respond to soil fertility changes under double-cropping rice (Oryza sativa L.) system in southern China paddy field. Therefore, the effects of different short-term (5-years) tillage management on characteristics of C utilization in rice rhizosphere and non-rhizosphere soils under double-cropping rice field in southern China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In the present study, NT treatment decreased SOC content in the paddy field compared to RT and CT treatments, suggesting that CH 4 emission from the paddy field with no-tillage practice decreased. Some results indicated that aerobic methanotrophs and anaerobic methanogens were obviously influenced by the rice root soil environment [14]. RT and CT treatments destroyed soil structure and reduced gas diffusivity at the plough layer; therefore, soil CH 4 uptake and CH 4 oxidation were decreased [26].…”
Section: Effects Of Tillage Management On Ch 4 and N 2 O Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, NT treatment decreased SOC content in the paddy field compared to RT and CT treatments, suggesting that CH 4 emission from the paddy field with no-tillage practice decreased. Some results indicated that aerobic methanotrophs and anaerobic methanogens were obviously influenced by the rice root soil environment [14]. RT and CT treatments destroyed soil structure and reduced gas diffusivity at the plough layer; therefore, soil CH 4 uptake and CH 4 oxidation were decreased [26].…”
Section: Effects Of Tillage Management On Ch 4 and N 2 O Emissionsmentioning
confidence: 99%
“…Furthermore, some results indicated that N 2 O emission from paddy fields with CT treatment was lower than that of NT treatment with crop residue incorporation [10,13]. Tang et al [14] showed that rice yield was decreased with NT practice, compared with CT and RT practices. Global warming potential (GWP) was generally considered a vital indicator for the effects of GHG emissions, with the GWP of CO 2 defined as 1.…”
Section: Introductionmentioning
confidence: 99%
“…Given that organic matter decomposition increases via microbial enzyme production [25], the slightly increased alkaline pH and decreased water content in spring [21] may have created the optimum conditions for invertase activity in the topsoil rhizosphere. Meanwhile, dissolved C content decreases with an increase in microbial biomass and C use in the rhizosphere [26], subsequently reducing invertase activity (Figure 6).…”
Section: Response Of Enzyme Activities In the Rhizosphere And Bulk So...mentioning
confidence: 99%
“…Research on the spatiotemporal variations and influencing factors of carbon sinks/sources in agroecosystems often centers on the analysis of differences in natural endowment, socio-economic policies, and field management practices to elucidate the mechanisms affecting carbon source-sink dynamics and pathways for reducing emissions. Additionally, a few scholars have explored the differences in net carbon sequestration under different farming practices and irrigation methods [24,25].…”
Section: Introductionmentioning
confidence: 99%